PENGARUH PERTUMBUHAN PERUSAHAAN, KEBIJAKAN HUTANG, KEPEMILIKAN MANAJERIAL DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN : STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR PADA BURSA EFEK INDONESIA - Muhamad Satrio Aditomo; Rinny Meidiyustiani (LPPM Universitas Bina Bangsa, 2023)
The value of a company is the ratio of its stock price to its book value. The high value of the company is an attraction for investors to invest in the company, it indicates that the company has good prospects in the future. The purpose of this study was to determine the effect of Company Growth, Debt Policy, managerial ownership and company size on company value. The population is a manufacturing company in the food and beverage sector listed on the Indonesia Stock Exchange (IDX) in the financial statements for the period 2017-2021. Samples were determined by purposive sampling technique with certain criteria and obtained samples of 11 companies. This study uses multiple linear regression analysis method assisted by SPSS Ver program.20. The results showed that the growth of the company and managerial ownership has a positive and significant effect on the value of the company, while the debt policy and the size of the company does not significantly affect significant the value of the company